Familias Fuertes: A Feasibility Study With Mexican Immigrants Living in Low-Income Conditions in the Southeastern United States. Issue 6 (November 2014) - Orpinas, Pamela; Reidy, Mary Clare; Lacy, Mary Elizabeth; Kogan, Steven M.; Londoño-McConnell, Angela; Powell, Gwynn
Families Fuertes (FF) is a seven-session, family-centered program for supporting positive youth development of Latino children aged 10 to 14 years. The Pan American Health Organization adapted it from the Strengthening Families Program for Parents and Youth for Spanish-speaking countries. The suitability of FF for recent immigrants to the United States is, however, unknown. This feasibility study assessed the appropriateness of FF with 12 low-income Mexican immigrant families residing in Georgia. Participants, a community liaison, and program staff evaluated (a) recruitment, retention, and evaluation strategies; and (b) the acceptability and promise of the curriculum. Recruitment and retention were very high; feedback of evaluation strategies was uniformly positive. Participants perceived that the program improved family relationships and that family members changed for the better. We detail practical and cultural adaptations to enhance the potential effectiveness of the program for this population. A version adapted to address acculturation-related stressors would increase the potential public health impact.